Understanding online purchase intention: the mediating role of attitude towards advertising - Hai Ho Nguyen; Bang Nguyen-Viet; Yen Thi Hoang Nguyen; Tin Hoang Le (Cogent Business & Management, 2022)
Recognizing the growth of Facebook and advertising on this platform in an emerging market, we conducted a study on the impact of Facebook advertising characteristics on the market's purchase intention. This study attempts to identify and test key factors that have a direct impact on customer online purchase intention for advertised products, and examines the mediating role of attitude towards advertising. In addition, for factors that have been shown in previous studies to have a direct impact on consumer purchase intention, such as entertainment, credibility, and personalization, the direct effects are also included in the model for further consideration. This study follows a quantitative approach through interviews with 477 participants. The questionnaires were distributed to the respondents by interviewers at milk tea and coffee shops in Ho Chi Minh City, Vietnam's largest city. Data were analyzed through structural equation modelling. Empirical results have shown an indirect effect of informativeness, privacy concerns, and irritation on purchase intention through attitudes towards advertising, however, the factors interact, personalization, entertainment, and credibility do not show an impact on attitudes towards advertising. Finally, factors such as entertainment, personalization, and credibility of Facebook ads are also found to have a significant positive effect on purchase intention. This study was successful in developing an empirical model for understanding online purchase intention with the mediating role of attitude towards advertising in emerging markets, specifically Vietnam. Therefore, the study provides essential insights for firms and marketers investigating issues related to online purchase intentions, and attitudes towards advertising.
Keywords: 650; Facebook; Vietnam; attitudes towards advertising; Facebook advertising; Online purchase intention